EDUKASI PEMANFAATAN PROBIOTIK ALAMI DARI KULIT NANAS (Ananas comosus L. Merr) BAGI KESEHATAN TUBUH DI SMA NEGERI 10 MEDAN - Purba, Jhan Saberlan; Marbun, Novarianti; Br Bangun, Sofia Eliasari; Dhini, Fitri Wahyu; Pertiwi, Diah (INSTITUT KESEHATAN DELI HUSADA, 2025)
Pineapple peel (Ananas comosus L. Merr) waste is abundant in Indonesia but has not been optimally utilized, despite containing beneficial compounds such as bromelain and flavonoids with potential as health products. The lack of public understanding regarding the processing of this waste forms the basis for this Community Service activity. This activity aims to educate students of SMA Negeri 10 Medan on the benefits of natural probiotics from pineapple peels and the method of converting them into a functional beverage. The method employed is interactive counseling, which includes lectures, question-and-answer sessions, and quizzes to enhance participants' understanding. Through this initiative, it is expected that the students' knowledge and awareness regarding the utilization of local natural resources will increase, fostering an interest in processing pineapple peel waste into a probiotic drink that is beneficial for health and promotes sustainability.